2014
DOI: 10.1007/s00464-014-3737-x
|View full text |Cite
|
Sign up to set email alerts
|

Transanal endoscopic microsurgery for surgical repair of rectovesical fistula following radical prostatectomy

Abstract: Rectovesical fistulas associated with wide, tough scar tissue due to multi-time attempt of surgical repair or any type of energy ablation should not be indicated for repair by TEM. However, for simple fistulas without tough, fibrotic surroundings, TEM can be indicated as a minimally invasive surgical option with very low morbidity, without any incision in healthy tissue for approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
0
19
1
Order By: Relevance
“…Several possible factors affecting results of URF repair have been reported [5,[8][9][10] . Some papers suggested that complicated fistulas with a large diameter, previous failed repair surgery, or previous irradiation are negative predictive factors for the successful closure of fistulas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several possible factors affecting results of URF repair have been reported [5,[8][9][10] . Some papers suggested that complicated fistulas with a large diameter, previous failed repair surgery, or previous irradiation are negative predictive factors for the successful closure of fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…The failure rates are 41, 13, 12, and 10% for the transanal, transabdominal, transanal sphincteric, and transperineal approaches, respectively, according to a systematic review [1] . Recently, Kanehira et al [9] reported transanal endoscopic surgery without interposition of a muscle flap for URF patients and showed excellent results on selected cases. Although their method is less invasive, they insist that URFs with wide, hard scar tissue due to multiple attempts at surgical repair or any type of energy ablation are not indicated for their procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The development of transanal endoscopic surgery, that was originally described to perform resection of early rectal tumors, and the increasing interest in minimally invasive surgery have led to use this technique for RVF repair (6)(7)(8). Its key points are the dissection of mucosa until the proper muscle is completely exposed, the resection of the mucosal layer and fistula tract and the closure of the defect by suturing (8).…”
Section: Discussionmentioning
confidence: 99%
“…Its key points are the dissection of mucosa until the proper muscle is completely exposed, the resection of the mucosal layer and fistula tract and the closure of the defect by suturing (8). The most important advantages it provides are excellent the visualization of the surgical field and surgery without incision in healthy tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The TEM approach has also been useful in the minimally invasive treatment of surgical complications such as recto-vaginal fistulas [7] and anastomotic dehiscence, opening a new horizon for applications of TEM.…”
mentioning
confidence: 99%